Improving customer satisfaction in service quality evaluation using the carter framework: A case study of SS Umrah and Travel in Indonesia - Hamzah Romzul Qurani; Nur Budi Mulyono (Journal of Multidisciplinary Academic Business Studies, 2025)
Purpose: This study aims to analyze the service quality of SS Umroh Travel and its impact on customer satisfaction by applying the SERVQUAL model, extended with the CARTER framework. Research methodology: Using a quantitative approach and survey method, data were collected from 240 respondents who used SS Umroh services. Results: Negative gaps were found in all service quality dimensions, with assurance showing the largest gap, followed by Reliability and Tangibility. The regression results indicated that empathy significantly influenced customer satisfaction, whereas strict compliance had a negative effect. Three priority areas for improvement were identified: Assurance, Empathy, and Tangibility. Recommended strategies include staff training, SOP development, improved accessibility, and monitoring systems, supported by the Plan–Do–Check–Act (PDCA) cycle for continuous quality improvement. Conclusion: SS Umroh Travel has a basic service system, but negative gaps indicate unmet customer expectations. Assurance and Empathy are critical to building trust and satisfaction, making their improvement vital for competitiveness. Limitations: The study is limited to one company, relies on self-reported surveys, and lacks longitudinal data, which reduces generalizability. Contribution: This study theoretically integrates SERVQUAL and CARTER in religious tourism service evaluation. Practically, it offers strategic recommendations for SS Umroh and similar operators to enhance their service quality and customer satisfaction.